2019
DOI: 10.13057/biodiv/d200819
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Phenotypic diversity of male pelung chickens in West Java Province, Indonesia

Abstract: Abstract. Asmara IY, Garnida D, Setiawan I, Partasasmita R. 2019. Short Communication: Phenotypic diversity of male pelung chickens in West Java Province, Indonesia. Biodiversitas 20: 2243-2248. Pelung chickens are indigenous chickens from Cianjur District, West Java Province, Indonesia. The male chickens have long and beautiful crowing and have a distinct body figure compared to other indigenous chickens. Chicken contests are conducted regularly as media to show singing ability and body performance of Pelung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This condition is relatively small compared to triglyceride levels in chickens in general. Some research reported that normal broiler blood triglyceride levels were less than 150 ml/dL [16,19,20]. The analysis results in the appendix show that the blood triglyceride profile in the starter phase was the least in the K3 treatment (59.833 mg/dL), while the triglyceride profile was the most in the K0 treatment (83.985 mg/dL).…”
Section: Resultsmentioning
confidence: 96%
“…This condition is relatively small compared to triglyceride levels in chickens in general. Some research reported that normal broiler blood triglyceride levels were less than 150 ml/dL [16,19,20]. The analysis results in the appendix show that the blood triglyceride profile in the starter phase was the least in the K3 treatment (59.833 mg/dL), while the triglyceride profile was the most in the K0 treatment (83.985 mg/dL).…”
Section: Resultsmentioning
confidence: 96%
“…Pelung is considered as specific local chicken which easily recognised by its long crowing character [7,14,15]. Unlike Kedu and Sentul chicken breed which recognised by its standard plumage colours, Pelung exist with many plumage colours types [16]. Blue colour in Sentul plumage and Black or brown colours in Black Kedu and Brown Kedu chicken breeds plumage [17].…”
Section: Resultsmentioning
confidence: 99%
“…The weight of a rooster is 3500 g on average, whereas a female is 3000 g on average (Mustofa et al 2021). Red and black were the primary plumage colors for male Pelung chickens (Asmara et al 2019b), while black and yellow-brown were commonly found in female chickens (Asmara et al 2019a). The Minister of Agriculture formally acknowledged that Pelung is an indigenous chicken breed in Indonesia that needs safeguarding and conservation by issuing Decree No.…”
Section: Methodsmentioning
confidence: 99%